El control del contenido en contratos estandarizados. Análisis de la prohibición de cláusulas abusivas bajo el artículo 1399 del Código Civil peruano - Vásquez Rebaza, Walter Humberto (2023)
One of the most important –and controversial– ways in which the legislator intervenes in standardized contracts (i.e., contracts with general contracting clauses and adhesion contracts) lies in the possibility for jurisdictional authorities to control their contractual content. The purpose of this intervention is to eliminate or substitute clauses effectively incorporated in them for being abusive or vexatious. This paper examines the discipline of content control provided by Article 1399 of the Civil Code, a rule that, despite having been unjustly relegated by national scholars, has enormous potential to achieve the protective purposes set by our Substantive Code, when correctly understood. On this occasion, we will first analyze the various legal rules contained in Article 1399, as well as their respective hypotheses and consequences. This analysis will be complemented by a practical application to concrete cases, allowing an understanding of the functioning of the normative provision. Secondly, the basis and importance of the article in question will be discussed, as well as its potential to become a notion capable of eradicating dysfunctional stipulations beyond the brief definition established by the Peruvian legislator in 1984 in Article 1398. Thirdly and lastly, we will develop which are the justifying circumstances capable of neutralizing, in each specific case, the abstractly vexatious nature of an allegedly abusive clause under Article 1399. This analysis takes on special relevance since its treatment by national scholars has been almost nonexistent.